Pengaruh Emotional Branding, Nilai Pelanggan, Dan Citra Merek Terhadap Loyalitas Pelanggan Starbucks Botani Square - Yohanes Raharja; Mumuh Mulyana (Jurnal Ilmiah Pariwisata Kesatuan, 2020)
This study aims to determine the effect of Emotional Branding, Customer Value, and Brand Image on Starbucks Customer Loyalty Coffee Botani Square Bogor. The type of research used is explanatory. The population in this study were the customers of Starbucks Coffee Botani Square Bogor, using the Hair et al theory, 190 respondents were taken as samples and the sampling technique used was purposive sampling. The data collection method uses questionnaires, interviews, and documentation. The measurement scale is used likert scale. The data analysis method used is the analysis of structural equation modeling (SEM) using the AMOS Ver program. 22. From the results of the study, Emotional Branding has a significant positive effect on Customer Loyalty Starbucks Botani Square. This is indicated by that the value of t arithmetic 4.165 is greater than 1.96 or there is a sign of *** on the value of P, while the value of the Customer has a significant positive effect on Customer Loyalty Starbucks Botani Square. This is indicated by that the value of t count 5.142 is greater than 1.96 or there is a sign of *** on the P value and Brand Image has a significant positive effect on Customer Loyalty Starbucks Botani Square. This is indicated by that the value of t count 3.570 is greater than 1.96 or there is a sign of *** on the value of P. While overall Emotional Branding, Customer Value and Brand Image have a positive and significant influence on Customer Loyalty Starbucks Botani Square. It is shown that the magnitude of the effect of Emotional Branding, Customer Value, and Brand Image on customer loyalty is positive with a total influence of 81.8%. Suggestions in this study, namely Starbucks Coffee Botani Square Bogor must add to their promotional media, and Starbucks must be able to make their website more interactive to make it more attractive. And Starbucks should start making new products or new formulas that can provide more benefits to consumers from consuming Starbucks products. And to increase customer loyalty, can be done by giving a promise or discount. Keywords : Emotional Branding, Customer Value, Brand Image and Customer Loyalty